Two drugs are better than one. A short history of combined therapy of ovarian cancer - Bukowska, Barbara; Gajek, Arkadiusz; Marczak, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2015)
Combined therapy of ovarian cancer has a long history. It has been applied for many years. The first drug which was commonly combined with other chemotherapeutics was cisplatin. It turned out to be effective given together with alkylating agents as well as with taxanes. Another drug which is often the basis of first-line therapy is doxorubicin. The use of traditional chemotherapy is often limited due to side effects. This is why new drugs, targeted specifically at cancer cells (e.g. monoclonal antibodies or epidermal growth factor receptor inhibitors), offer a welcome addition when used in combination with conventional anticancer agents. Drugs applied in combination should be synergistic or at least additive. To evaluate the type of interaction between drugs in a plausible sequence, isobolographic analysis is used. This method allows one to assess whether the two agents could make an efficient combination, which might improve the therapy of ovarian cancer.